Magtayo Instructional Framework in Teaching Social Constructivist Strategies for Junior High School Social Studies - Pimentel, Marivic (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2024)
The study explored the social constructivist practices and experiences in teaching social constructivist strategies of Junior High School Social Studies teachers. The study used a qualitative single exploratory case study. Thirteen Social Studies teachers who were purposely selected based on the results of the pre-assessment survey participated to share their social constructivist practices and experiences. Interviews, classroom observation, lesson plans, and FGD were used in this research to collect data, and a thematic three-phase analysis was done. Based on the findings, the Social Studies teacher's social constructivist teaching practices in terms of teaching, assessment, and resources meet the needs of students and give them opportunities to express their constructions of knowledge, interact in social groups, give students a chance to correct their wrong constructions and broaden their construction of knowledge through various resources. The evolved experiences are essential to improving the teaching and learning process, such as misconceptions about social constructivist strategies, lowering students’ interactions in flexible learning, and high engagement of students’ learning. Thus, the Magtayo instructional framework is designed to serve as a guide for employing social constructivist strategies.